MSG488 – Mathematical Algorithms for Computer Graphics - PPSM, Pusat Pengajian Sains Matematik (2022)
First Semester Examination 2021/2022 Academic Session February 2022 MSG488 – Mathematical Algorithms for Computer Graphics Duration : 2 hours